'How do you feel about a disease?' The effect of psychological distance towards a disease on health communication. Issue 1 (2nd January 2019) - Kim, Dong Hoo
ABSTRACT: Based on construal level theory, this research addresses the moderating role of an individual's psychological distance towards a disease in the effectiveness of advertising messages framed by two distinctive construal level terms (high-level and low-level). In Experiment 1, two different disease types (bronchitis/distant disease vs. influenza/proximal disease) were featured, with the result that an advertisement with high-level construal terms was more persuasive for a psychologically distant disease (bronchitis) than for a psychologically proximal disease (flu). The reverse was true for an ad framed with low-level construal terms. To replicate Experiment 1 and further test the hypothesis, in Experiment 2, the perceived distance individuals have towards one disease (cancer) was measured and used as independent variable. Consistent with the results from Experiment 1, the low-level construal messages were more effective under the psychologically close condition than the psychologically distant condition. Reverse was true for the high-level construal messages.